2018
DOI: 10.1111/ped.13675
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden of pediatric primary immunodeficiency

Abstract: The rate of psychopathology was similar in patients with PID and JIA and higher than the controls. Some of the disease-related factors were associated with the frequency of mood disorders in the PID patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…As expected based on the general demographic patterns associated with JIA, study populations included a majority of female patients (range 52-81%) with the exception of one study. 23 Among the included pediatric studies, the mean age was 6.9 to 15.5 years and the age range in the adult studies was 18 to 73 years. Most studies did not report race and/or ethnicities.…”
Section: Population Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…As expected based on the general demographic patterns associated with JIA, study populations included a majority of female patients (range 52-81%) with the exception of one study. 23 Among the included pediatric studies, the mean age was 6.9 to 15.5 years and the age range in the adult studies was 18 to 73 years. Most studies did not report race and/or ethnicities.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Most studies that used validated screens for depressive symptoms reported prevalences of clinically significant symptoms in the range of 7-36% in children with JIA. [23][24][25][26]28,29,35,38,39,41,46,47 Reda et al used the MINI-KID psychiatric interview and reported that 93% of the patients had dysthymic disorder while 3% had major depressive disorder. 30 El Najjar et al found that all JIA patients scored above the cut-off for clinically significant symptoms on the CES-DC questionnaire.…”
Section: Prevalence Of Depressive Symptoms In Jiamentioning
confidence: 99%
See 3 more Smart Citations